El análisis de los protagonistas sobre la administración de los recursos naturales - Ravnborg, Helle Munk; Guerrero, M.P. (1997)
Natural resource management problems in agriculture often transcend field or farm boundaries. What happens in one part of landscape depends on management practices in another. Pest and disease problems in crops, soil erosion, problems related to quantity and quality of water are all examples of this temporal and spacial interdependency. Some form of collective action among landscape users is needed to coordinate how different landscape patches are managed in time and space. CIAT is working to enhance such collective action in the Andean hillsides of southern Colombia, using stakeholder analysis.